2020
DOI: 10.1101/2020.03.21.20040329
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiological parameters of coronavirus disease 2019: a pooled analysis of publicly reported individual data of 1155 cases from seven countries

Abstract: medRxiv preprint generally longer incubation and serial interval of less severe cases suggests a high risk of longterm epidemic in the absence of appropriate control measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
145
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(159 citation statements)
references
References 29 publications
(72 reference statements)
13
145
0
1
Order By: Relevance
“…These cannot be considered representative of the countries from which they were drawn. The same conclusion applies to the studies by Ma et al [25], Ferretti et al…”
Section: Methods Used For Estimating the Serial Interval And The Genesupporting
confidence: 78%
See 1 more Smart Citation
“…These cannot be considered representative of the countries from which they were drawn. The same conclusion applies to the studies by Ma et al [25], Ferretti et al…”
Section: Methods Used For Estimating the Serial Interval And The Genesupporting
confidence: 78%
“…Ganyani et al [24] used a Markov chain Monte Carlo (MCMC) approach for the same purpose. Ma et al [25] made an effort to overcome this issue by setting out a clear methodology for ensuring that the order of transmission was correct. • Generally, publicly available datasets were used in the studies under review.…”
Section: Methods Used For Estimating the Serial Interval And The Genementioning
confidence: 99%
“…The inverse problem of the infectiousness profile was solved by assuming an incubation period from Lauer et al 16 The serial interval predicted using this estimate is shown in dotted red line. While Ma et al 11 , Du et al 10 , showed fits to their serial interval data, He et al 7 made a similar estimate for the infectiousness based on the smaller data size of 77 patients. Figure 2.…”
Section: Bootstrappingmentioning
confidence: 97%
“…Inferring infectiousness from serial interval. We combined the serial interval data of 689 patients from Ma et al 11 , 485 patients from Du et al 10 , and 77 patients from He et al, 7 to build a larger data set. The inverse problem of the infectiousness profile was solved by assuming an incubation period from Lauer et al 16 The serial interval predicted using this estimate is shown in dotted red line.…”
Section: Bootstrappingmentioning
confidence: 99%
“…Asymptomatic carriers, who reportedly bear equivalent viral loads to patients exhibiting symptoms (5), originally estimated at 18% of infected individuals on the Diamond Princess cruise ship (6), now include a reported majority of infected sailors on the Theodore Roosevelt (7) and 79% of mothers who tested positive in an obstetrics ward in New York (8). Population surveys in Italy, Iceland, and China have reported intermediate values around 45% (9)(10)(11). High rates of asymptomatic carriers might result in undetected transmission chains that could reduce the efficacy of forward-tracing.…”
Section: Introductionmentioning
confidence: 99%